Investigation of soft and living matter using a micro-extensional rheometer. (4th December 2020) - Dubey, Sushil; Veer, Sukh; Seshagiri Rao, R V; Kalelkar, Chirag; Pullarkat, Pramod A
Abstract: Rheological properties of a material often require to be probed under extensional deformation. Examples include fibrous materials such as spider-silk, high-molecular weight polymer melts, and the contractile response of living cells. Such materials have strong molecular-level anisotropies which are either inherent or are induced by an imposed extension. However, unlike shear rheology, which is well-established, techniques to perform extensional rheology are currently under development and setups are often custom-designed for the problem under study. In this article, we present a versatile device that can be used to conduct extensional deformation studies of samples at microscopic scales with simultaneous imaging. We discuss the operational features of this device and present a number of applications.